2021
DOI: 10.1037/apl0000519
|View full text |Cite
|
Sign up to set email alerts
|

Referents or role models? The self-efficacy and job performance effects of perceiving higher performing peers.

Abstract: What are the effects of perceiving peers’ higher performance? Social–cognitive theory emphasizes the positive influence that perceiving higher performers can have on observer task and job performance (because observational learning from role models enhances self-efficacy). Social comparison theory emphasizes the negative self-evaluations that accompany perceiving higher performers, which should under many circumstances reduce self-efficacy and subsequent task and job performance. To more fully understand the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 69 publications
1
67
0
Order By: Relevance
“…In this regard, as a fourth contribution, our study also extends the research focusing on how others treat higher performers. This latter stream of research has particularly focused on whether higher (lower) performers experience victimization at work (Aquino & Bommer, 2003;Campbell et al, 2017;Downes et al, 2020;Jensen et al, 2014;Kim & Glomb, 2014;Lam et al, 2011). Our study suggests that performing higher ROCB is rewarding, and that leaders are more likely to reciprocate this higher relative contribution in a fair and proportional manner by providing higher LMX treatment than average.…”
Section: Introductionmentioning
confidence: 76%
“…In this regard, as a fourth contribution, our study also extends the research focusing on how others treat higher performers. This latter stream of research has particularly focused on whether higher (lower) performers experience victimization at work (Aquino & Bommer, 2003;Campbell et al, 2017;Downes et al, 2020;Jensen et al, 2014;Kim & Glomb, 2014;Lam et al, 2011). Our study suggests that performing higher ROCB is rewarding, and that leaders are more likely to reciprocate this higher relative contribution in a fair and proportional manner by providing higher LMX treatment than average.…”
Section: Introductionmentioning
confidence: 76%
“…The concept of self-efficacy was initially proposed by Bandura (1977) , which refers to an individual’s judgment of his or her capability of engaging in certain activities. Self-efficacy can generally be classified into two types, that is, general self-efficacy and domain-specific self-efficacy ( Alisic et al, 2020 ; Downes et al, 2021 ). Occupational self-efficacy belongs to domain-specific self-efficacy, which is developed based on self-efficacy, and is generally defined as “the generic terms for a series of behavioral efficacy judgments about occupational adjustments and range of choice during the job selection of individuals” ( Lent and Hackett, 1987 ; De Clercq et al, 2019 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The low work efficiency often has a negative effect on the business efficiency and profitability of the entire organization, which makes the discussion on employees’ job performance become essential ( De Clercq et al, 2019 ; Lee et al, 2021 ). Job performance has always been the focus within the organization ( Downes et al, 2021 ). During the pandemic, organizational performance is the key factor to establish the survival capability of the organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, prior research has shown pronounced differences both in individual supervisors' ability to influence their team members (Buengeler et al, 2016; Triana et al, 2017) and in individual members' susceptibility toward supervisory influence (Rank et al, 2009; Wellman et al, 2019). Social learning theory supports this notion, arguing that processes of behavioral mimicry hinge on both a potential role model's and an observer's characteristics (Bandura, 1977, 1986; Downes et al, 2021). Hence, different supervisors' initiating structure and consideration may yield strikingly different consequences for their individual members' respective behaviors, depending on attributes of both the supervisor enacting this behavior and the member targeted with it.…”
Section: Inroductionmentioning
confidence: 99%